Deep water recycling through time. (10th November 2014) - Magni, Valentina; Bouilhol, Pierre; van Hunen, Jeroen
Abstract We investigate the dehydration processes in subduction zones and their implications for the water cycle throughout Earth's history. We use a numerical tool that combines thermo‐mechanical models with a thermodynamic database to examine slab dehydration for present‐day and early Earth settings and its consequences for the deep water recycling. We investigate the reactions responsible for releasing water from the crust and the hydrated lithospheric mantle and how they change with subduction velocity (vs), slab age (a) and mantle temperature (Tm). Our results show that faster slabs dehydrate over a wide area: they start dehydrating shallower and they carry water deeper into the mantle. We parameterize the amount of water that can be carried deep into the mantle, W (×105 kg/m2), as a function of vs (cm/yr), a (Myrs), and Tm (°C): <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh2t272tkt" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />W=1.06vs+0.14a−0.023Tm+17</alternatives>. We generally observe that a 1) 100°C increase in the mantle temperature, or 2) ∼15 Myr decrease of plate age, or 3) decrease in subduction velocity of ∼2 cm/yr all have the same effect on the amount of water retained in the slab at depth, corresponding to a decrease of ∼2.2×105 kg/m2 of H2O. We estimate that for present‐day conditions ∼26% of the global influx water, or 7×108 Tg/Myr of H2O, is recycled into the mantle. Using a realistic distribution of subduction parameters, we illustrate that deep water recycling might still be possible in early Earth conditions, although its efficiency would generally decrease. Indeed, 0.5–3.7 × 108 Tg/Myr of H2O could still be recycled in the mantle at 2.8 Ga.